Biocontrol de la marchitez Vascular del babaco, con Trichoderma spp. mediante dos métodos de inoculación - Jarro Samaniego, Gabriela Yaqueline (2016)
In this research work the biocontrol of vascular wilt of babaco was assessed (Vasconcellea heilbornii Heilborn), using Trichoderma in the greenhouse, and field. Biological control agents used in this essay were: two isolates of Trichoderma (ECM3 y ECM6), at a concentration of 106 UFC/mL-1, and the pathogen was isolated from Fusarium oxysporum (QUI2), at a concentration of 106 CFU / mL-1. For greenhouse conditions, was used a completely randomized design with 4 treatments (T0 = inoculation with distilled water; T1 = Inoculation with Fusarium oxysporum, T2 = Inoculation with Trichoderma Fusarium oxysporum + (ECM3), T3 = Inoculation of Fusarium oxysporum + Trichoderma (ECM6)) and 6 replicates, through two methods of inoculation, to the substrate and by immersion of roots, while for field conditions only inoculation method was used by dipping roots, this method reported the best results in greenhouse conditions. The method of inoculation by dipping roots under greenhouse conditions presented a biocontrol of 41,7 % y 38,1 % for isolated ECM3 and ECM6 respectively, while with inoculation method to the substrate presented a biocontrol of 40.9% with the ECM 3 isolated and 37.7% with the ECM6 isolated. In field conditions a biocontrol of 37.5% and 33.3% was obtained, also it could demonstrate higher growth and a higher number of leaves in seedlings inoculated with Trichoderma. Keywords: Biocontrol, Trichoderma, Fusarium.